Cerebral Vasospasm in Traumatic Brain Injury - Daniel R. Kramer; Jesse L. Winer; B. A. Matthew Pease; Arun P. Amar; William J. Mack (Neurology Research International)
Vasospasm following traumatic brain injury (TBI) may dramatically affect the neurological and functional recovery of a vulnerable patient population. While the reported incidence of traumatic vasospasm ranges from 19%–68%, the true incidence remains unknown due to variability in protocols for its detection. Only 3.9%–16.6% of patients exhibit clinical deficits. Compared to vasospasm resulting from aneurysmal SAH (aSAH), the onset occurs earlier and the duration is shorter. Overall, the clinical course tends to be milder, although extreme cases may occur. Traumatic vasospasm can occur in the absence of subarachnoid hemorrhage. Surveillance transcranial Doppler ultrasonography (TCD) has been utilized to monitor for radiographic vasospasm following TBI. However, effective treatment modalities remain limited. Hypertension and hypervolemia, the mainstays of treatment of vasospasm associated with aSAH, must be used judiciously in TBI patients, and calcium-channel blockers have offered mixed clinical results. Currently, the paucity of large prospective cohort studies and level-one data limits the ability to form evidence-based recommendations regarding the diagnosis and management of vasospasm associated with TBI.